Effects of Pre-Synchronization With Prostaglandin F2α and a Progestin, and Delayed Insemination on Pregnancy Rates With Sexed Semen in Replacement Beef Heifers - Oosthuizen, Nicola; Porter, Kristina; Burato, Samir; Goncalves, Lucas M.; Pohler, Ky G.; Fontes, Pedro L. P.; Lamb, G. Cliff (Frontiers in Animal Science, 2022)
To determine effects of presynchronization and delayed fixed-time artificial insemination (TAI) on pregnancy rates (PR/AI) with sexed semen, 1,844 beef heifers were enrolled in a completely randomized design at 12 locations. Within location, heifers were randomly assigned to one of five treatments: 1 and 2), heifers were administered prostaglandin F2α (PGF) on Day -7, gonadotropin-releasing hormone (GnRH) and a CIDR insert on Day 0, PGF at CIDR removal on Day 7, and a second injection of GnRH at TAI 72 hours later with either conventional (CTRL72-CNV; n=359) or sexed semen (CTRL72-SEX; n=363); 3 and 4), treated the same as CTRL72 but received a CIDR insert on Day -7 at PGF administration and TAI at 60 hours with either conventional (CIDR60-CNV; n=384) or sexed semen (CIDR60-SEX; n=366); 5), treated the same as CIDR60 but had TAI delayed to 72 hours with sexed semen (CIDR72-SEX; n=372). Estrus detection patches were applied to all heifers on Day 7 and were evaluated for activation at TAI. Estrus expression did not differ (P=0.92) between CIDR60 and CIDR72 heifers but was greater (P<0.001) in CIDR60 and CIDR72 heifers compared with CTRL72 heifers (87.5 and 87.7 vs. 73.6%, respectively). Among treatments, PR/AI differed (P<0.001) and were greater (P≤0.003) in CTRL72-CNV and CIDR60-CNV heifers than CIDR60-SEX and CIDR72-SEX heifers (51.6 and 48.1 vs. 37.5 and 25.3%, respectively). In addition, PR/AI were greater (P<0.001) in CTRL72-SEX and CIDR60-SEX heifers when compared with CIDR72-SEX (42.0 and 37.5 vs. 25.3%, respectively) heifers but only tended (P=0.09) to differ between CTRL72-SEX and CIDR60-CNV heifers. No differences (P=0.33) were determined between CTRL72-CNV and CIDR60-CNV or between CTRL72-SEX and CIDR60-SEX heifers (P=0.22). In conclusion, no differences were determined between heifers presynchronized with only PGF and those presynchronized with PGF and a CIDR insert when inseminated with either conventional or sexed semen. Therefore, use of a CIDR insert for an additional 7 days was not beneficial to PR/AI when heifers were TAI at 60 hours with either conventional or sexed semen. Furthermore, delaying TAI to 72 hours with sexed semen after presynchronization with both PGF and a CIDR insert has a negative impact on PR/AI.